2018
DOI: 10.1617/s11527-018-1212-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using recycled concrete aggregates for half-warm mix asphalt

Abstract: The present study describes a laboratory investigation on the feasibility of reusing construction and demolition waste as recycled concrete aggregate (RCA) to manufacture half-warm mix asphalt (HWMA) instead of natural aggregates. In this investigation, semi-dense HWMA for the binder course, type AC 22 bin S, was analysed. Percentages of 0% (control mixture), 55%, and 100% RCA were used instead of natural aggregates (hornfels). Cationic bitumen emulsion, type C60B4, was used to manufacture the aforementioned m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In light of the moisture sensitivity test being particularly significant for nations that experience cold weather, the obtained findings are quite encouraging and meaningful for RCA usage. The obtained results confirmed previous investigations [10,51,56]. In addition, the experimental findings showed that all TSR values for mixes, including different kinds of untreated CRCA with varying percentages, are higher than the minimum criteria for a previous study, registering an efficient outcome for the mixes that included RCA [57].…”
Section: Evaluation Of Moisture Sensitivitysupporting
confidence: 88%
“…In light of the moisture sensitivity test being particularly significant for nations that experience cold weather, the obtained findings are quite encouraging and meaningful for RCA usage. The obtained results confirmed previous investigations [10,51,56]. In addition, the experimental findings showed that all TSR values for mixes, including different kinds of untreated CRCA with varying percentages, are higher than the minimum criteria for a previous study, registering an efficient outcome for the mixes that included RCA [57].…”
Section: Evaluation Of Moisture Sensitivitysupporting
confidence: 88%
“…Bituminous mixtures can be manufactured using recycled aggregates such as construction and demolition waste (C&DW) [5] or reclaimed asphalt pavement (RAP). If RAP is used in the manufacture of WMA or HWMA, additional environmental benefits could be achieved, such as reduced waste, conservation of natural resources [6], and reduced consumption of aggregates and bitumen.…”
Section: Mixturementioning
confidence: 99%
“…This gave rise to the concept of sustainable construction which is understood as "ensuring the provision of current built environment needs without compromising resources needed to meet the needs of future generations. [7]" Hence, in achieving the objectives of sustainable construction in the road pavement industry, two main approaches have been followed -1) the development of new asphalt mixing and laying technologies and 2) the adoption of residues (wastes) and industrial by-products [8]. The adoption of waste materials that otherwise constitutes an environmental nuisance performs two roles in the achievement of sustainability.…”
Section: Introductionmentioning
confidence: 99%